Towards Future Internet services through crowdsourcing-based sensor platforms. (1st January 2013) - Zeiger, Florian; Boufidis, Zachos
Crowdsourcing initiatives accommodate the trend to transition from mere resource pooling, which has been successfully applied in technical domains such as grid computing and cognitive radio networks, to human resource pooling, with people contributing to a common purpose. Future Internet emerges as a paradigm that will incorporate crowdsourcing in many forms, with participatory mobile sensor networks being a prominent representative. In such networks, citizens carry small portable devices that provide sensor readings on demand, for example, for air quality monitoring. Whereas a multiplicity of research and industrial efforts has tackled the issue of connecting sensors and producing meaningful data over a plethora of deployed sensors, few initiatives have progressed beyond field-testing, partially due to underestimating the importance of service engineering aspects. This note aims at highlighting the objectives to be fulfilled and the necessary capabilities of sensor platforms towards the provision of Future Internet services built on top of crowdsourcing facilities.